Communicating Effectively in English: Oral Communication for Non-Native Speakers - Porter, Patricia A. (Belmont Wadsworth Publishing Company, 1985)
This book has been designed to help advanced-level, non-native speakers of English gain proficiency in speaking and listening. We believe that students can best learn communication skills by extensive practice. The book thus takes an interactive, experiential approach to learning.
Keywords: English Practice